2002
DOI: 10.1159/000054957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Nicotine Administration on Cognitive Event-Related Potentials in Tacrine-Treated and Non-Treated Patients with Alzheimer’s Disease

Abstract: Earlier studies of cognitive event-related brain potentials (ERPs) reporting diminished amplitudes and delayed latencies of the P300 potential in dementia of the Alzheimer type (DAT), together with independent findings of the P300- and performance-enhancing properties of nicotine in normal adults, stimulated this study to explore the single-dose effects of nicotine on auditory and visual P300s in DAT. Thirteen patients, 6 currently receiving treatment with the cholinesterase inhibitor tacrine (tetrahydroaminoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…This suggests that the increase of these peptides may reflect elevated precursor synthesis, consistent with the elevated preproenkephalin mRNA levels in the striatum after chronic nicotine application (15). Another class of opioid peptides, dynorphins derived from PDYN including dynorphin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and dynorphin(1-8), was not modulated by chronic nicotine. This is consistent with previous literature linking PDYN peptides to aversive states associated with drug withdrawal (47), which were not induced in our experiment.…”
Section: Table I Changed Prohormone-derived Peptides and Unchanged Knmentioning
confidence: 74%
See 1 more Smart Citation
“…This suggests that the increase of these peptides may reflect elevated precursor synthesis, consistent with the elevated preproenkephalin mRNA levels in the striatum after chronic nicotine application (15). Another class of opioid peptides, dynorphins derived from PDYN including dynorphin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and dynorphin(1-8), was not modulated by chronic nicotine. This is consistent with previous literature linking PDYN peptides to aversive states associated with drug withdrawal (47), which were not induced in our experiment.…”
Section: Table I Changed Prohormone-derived Peptides and Unchanged Knmentioning
confidence: 74%
“…various aspects of neurochemical transmission and has a strong impact on diverse physiological processes (2), resulting in drug-seeking and drug-taking behaviors for normal smokers and for a considerable number of patients suffering from schizophrenia and Alzheimer disease, who use nicotine for self-medication (3,4). The dorsal striatum (DS) 1 is one of the key brain regions that has been associated with neural regulation during chronic nicotine exposure (5).…”
mentioning
confidence: 99%
“…As with amplitude, several studies reported no effect on N100 latency (Ilan & Polich, 1999Knott et al, 1999a;Knott et al, 2002;Le Houezec et al, 1994;Michel et al, 1988). Houlihan et al (2001) reported that smoking/ nicotine shortened N100 latency to both memory-set and probe stimuli in a Sternberg-type task.…”
Section: Exogenous Components In Studies Having a Taskmentioning
confidence: 98%
“…Regarding effects for imperative stimuli (either with or without a warning stimulus), several studies reported no effects of nicotine on either exogenous ERP components or performance (Ilan & Polich, 1999Knott, 1985;Knott et al, 2002;Le Houezec et al, 1994;Michel at al., 1988). Others reported that smoking/nicotine facilitated performance in the absence of effects on exogenous ERP components (Knott, 1986;Knott et al, 1999a).…”
Section: Relation To Performancementioning
confidence: 99%
See 1 more Smart Citation